Close-in Super-Earths: The first and the last stages of planet formation in an MRI-accreting disc. Issue 2 (5th January 2019) - Jankovic, Marija R; Owen, James E; Mohanty, Subhanjoy
ABSTRACT: We explore in situ formation and subsequent evolution of close-in super-Earths and mini-Neptunes. We adopt a steady-state inner protoplanetary gas disc structure that arises from viscous accretion due to the magneto-rotational instability (MRI). We consider the evolution of dust in the inner disc, including growth, radial drift, and fragmentation, and find that dust particles that radially drift into the inner disc fragment severely due to the MRI-induced turbulence. This result has two consequences: (1) radial drift of grains within the inner disc is quenched, leading to an enhancement of dust in the inner regions that scales as dust-to-gas-mass-flux-ratio at ∼1 au; (2) however, despite this enhancement, planetesimal formation is impeded by the small grain size. Nevertheless, assuming that planetary cores are present in the inner disc, we then investigate the accretion of atmospheres on to cores and their subsequent photoevaporation. We then compare our results to the observed exoplanet mass–radius relationship. We find that (1) the low gas surface densities and high temperatures in the inner disc reduce gas accretion on to cores compared to the minimum mass solar nebula, preventing the cores from growing into hot Jupiters, in agreement with the data; (2) however, our predicted envelope masses are still typically larger than observed ones. Finally, we sketch a qualitative picture of how grains may grow and planetesimals form in the inner disc if grain effects on the ionization levels and the MRI and the back reaction of the dust on the gas (both neglected in our calculations) are accounted for.